A review on adsorbent/catalyst application for mercury removal in flue gas: Effect of sulphur oxides (SO2, SO3). (10th December 2020) - Zhang, Huicong; Wang, Tao; Zhang, Yongsheng; Wang, Jiawei; Sun, Baomin; Pan, Wei-Ping
Abstract: Mercury is harmful to the human body and to the ecological environment. Mercury emission from coal-fired power plants is one of the main sources of anthropogenic mercury emissions. Adsorbents and catalysts are popular materials developed to capture mercury from flue gas. Sulphur oxides (SO2, SO3 ) are the main components of flue gas; their concentration is more than 3 orders of magnitude higher than that of mercury. Sulphur oxides have a significant effect on mercury adsorption and catalytic processes. However, the effect mechanisms of sulphur oxides on mercury removal by adsorbents/catalysts are not uniform. In this review, the effects of SO2 and SO3 on the mercury removal process by adsorbents/catalysts are provided separately, and the suggested influence mechanisms are also summarized. SO2 has a two-sided effect on the performance of mercury removal by adsorbents and catalysts. Oxidation and activated adjacent sites are considered to be the main reasons for the promotion effect of SO2 . Competitive adsorption, active consumption and sulphate deposition are the main reasons for inhibition of mercury removal by SO2 . O2, H2 O, SO2 concentration and temperature have an impact on the effect of SO2 on mercury removal. SO3 can enhance the mercury removal efficiency of metal oxides-containing materials by increasing mercury oxidation rate. This review aims to promote a basic understanding of the effect of sulphur oxides on the mercury removal process and outline the future research direction of sorbents/catalysts for mercury removal, thereby advancing the research, development and application of materials with high sulphur resistance ability and removal efficiency. Graphical abstract: Image 1 Highlights: The promotion effect of SO2 is achieved by oxidation and adjacent sites activation. Inhibition reasons: competitive adsorption, activity consumption, sulphate deposition. SO3 can enhance mercury removal efficiency of metal oxide supported material. Gas components and temperature influence the effect of SO2 on mercury removal. Sulphur-resistant and magnetic metals enhance the practicality of adsorbents/catalysts.